2021
DOI: 10.1364/oe.421782
|View full text |Cite
|
Sign up to set email alerts
|

Temperature self-calibrated pH sensor based on GO/PVA-coated MZI cascading FBG

Abstract: A temperature self-calibrated potential of hydrogen (pH) sensor based on the single mode fiber-tapered dual core photonic crystal fiber-single mode fiber (SMF-TDCPCF-SMF) structure cascaded with a fiber Bragg grating (FBG) is proposed and demonstrated. The TDCPCF structure formed Mach-Zehnder interferometer (MZI) is modified with a coating of graphene oxide/polyvinyl alcohol (GO/PVA) hybrid hydrogel to realize the measurement of pH, and the uncoated FBG is used to calibrate temperature. In our experiment, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Obviously, it does not accurately detect the pH of the liquid environment. The GO/PVA-based sensor [ 18 ] cascaded the MZI and FBG to form a temperature self-calibrating pH sensor with excellent stability and good repeatability. Although this reduces temperature crosstalk during testing, it cannot ensure detection for universal pH conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, it does not accurately detect the pH of the liquid environment. The GO/PVA-based sensor [ 18 ] cascaded the MZI and FBG to form a temperature self-calibrating pH sensor with excellent stability and good repeatability. Although this reduces temperature crosstalk during testing, it cannot ensure detection for universal pH conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The surface plasmon resonance (SPR) sensor realizes the high sensitivity detection of pH by utilizing a characteristic of the sensitive film: expanding/contracting with the change of pH. Yan et al [ 18 ] reported a pH sensor with a Mach–Zehnder interferometer (MZI) cascaded with a fiber Bragg grating (FBG), by coating the graphene oxide/polyvinyl alcohol (GO/PVA)-sensitive film for pH detection, while the FBG was used for temperature calibration, which realized the temperature-self-calibrating pH monitoring. However, the disadvantages of complex optical fiber structures and fabrication processes have hindered their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…By differentiating ( 4) to (7), the wavelength shifts of the four sets of spectrum dips caused by the variation of strain ( ε Δ ) and temperature ( T Δ ) are determined by [21] ( )…”
Section: Cos Coscos Cos Cosmentioning
confidence: 99%
“…In-fiber Mach-Zehnder interferometers (MZIs) have been studied recently for various sensing applications such as the sensing of strain [1][2][3][4][5], temperature [6], pH [7,8], pressure [9,10], curvature [11,12], humidity [13], refractive index [14][15][16], and magnetic field [17,18]. An in-fiber MZI can be manufactured with multiple methods, for instance, using down-tapering structures [3], up-tapering structures [1], core-offset splicing structures [14] or simply splicing fibers with mismatched cores [4].…”
Section: Introductionmentioning
confidence: 99%
“…(5) Owing to the wavelength modulation, changes in the light source intensity, link loss, and the electrical signal intensity of an optical fiber sensing system will not influence the measurement results. Therefore, FBG sensors are widely used to monitor physical parameters such as temperature, (6,7) strain, (8) and displacement in the aerospace, civil engineering, petroleum, and petrochemical fields. (9)(10)(11) Accurate wavelength demodulation is the key to FBG sensing systems.…”
Section: Introductionmentioning
confidence: 99%